Violência por parceiro íntimo na gestação e tempo de retorno das atividades sexuais após o parto: análise da coorte de pré-natal brisa - ABREU, Liendne Penha (2023)
Intimate partner violence (IPV) during pregnancy can trigger obstetric complications and harm the woman's physical and psychological health. In the postpartum period, the return to sexual activities usually occurs around the 12th week, however, several factors can influence sexual function and the time of return. When a woman is exposed to violence, negotiations regarding sexual practices are likely to become more challenging. The objective of this study was to analyze whether there is an association between IPV during pregnancy and time to return to sexual activity after childbirth. A longitudinal study was carried out with data from the Prenatal Cohort of 2010, called BRISA, in São Luís - MA, conducted with 665 women. IPV during pregnancy was measured using a violence against women instrument created and validated by the World Health Organization, categorized into those who did not suffer violence and those who suffered IPV during pregnancy. The time to return to sexual activities after childbirth was investigated using a structured questionnaire, categorized into up to 3 months and after 3 months. A Directed Acyclic Graph (DAG) was prepared to indicate a minimum set of adjustment variables in order to minimize possible confounding biases. Crude and adjusted logistic regression models were used to investigate whether there is an association between IPV during pregnancy and time to return to sexual activity after childbirth. The odds ratio (OR) was calculated with their respective 95% confidence intervals (95% CI). The prevalence of intimate partner violence during pregnancy was 24.06%. The prevalence of women who returned to sexual activity within 3 months after childbirth was 67.96%. When analyzing the association between exposure and outcome, it was observed that there was no association in the crude model (OR: 0.88; 95% CI: 0.60 – 1.30) nor in the adjusted model (OR: 1.00; CI 95%: 0.61 – 1.63). However, this study contributes to filling gaps in scientific knowledge about the negative outcomes of violence during pregnancy, suggesting new perspectives and ways to expand comprehensive care for women's health. In addition, it emphasizes the need to sensitize health professionals, especially nurses, for the active search and identification of cases of violence in all phases of the pregnancy- puerperal cycle.